From genetics to treatment of eosinophilic esophagitis. Issue 5 (October 2015) - Cianferoni, Antonella; Spergel, Jonathan M.
<x xml:space="preserve">Abstract</x> Purpose of review Eosinophilic Esophagitis (EoE) is an emerging chronic atopic disease. Recent advances in understanding its genetic and molecular biology pathogenesis may lead to a better management of the disease Recent findings EoE is an atopic disease. Most of the patients affected by EoE have other atopic diseases such as allergic rhinitis, asthma, IgE-mediated food allergies and/or atopic dermatitis. The local inflammation is a T helper type 2 (Th2) flogosis, which most likely is driven by a mixed IgE and n-IgE-mediated reaction to food and/or environmental allergens. Epidemiological studies show that EoE is an atopic disease with a strong genetic component. Genetic studies have shown that EoE is associated with single nucleotide polymorphism on genes, which are released by the epithelium and important in atopic inflammation such as thymic stromal lymphopoietin located (TSLP) close to the Th2 cytokine cluster [interleukin (IL)-4, IL-5, IL-13] on chromosome 5q22, Calpain 14, EMSY, and Eotaxin3. When the EoE diagnosis is made, it is imperative to control the local eosinophilic inflammation not only to give symptomatic relief to the patient, but also to prevent complications such as esophageal stricture and food impaction. Summary EoE is treated like many other atopic diseases with a combination of topical steroids and/or food antigen avoidance. The new understanding of EoE may lead to more specific and definitive treatments of EoE.